Development of Islamic Value-Based Economics from a Sharia Economic Perspective - Intan Permata Sari; Mohammad Fattah (Ushul Al-Hukm: Jurnal Syariah dan Hukum Islam, 2025)
Modern economics, developed within a positivistic paradigm, often neglects ethical, spiritual, and social dimensions, giving rise to various problems such as inequality and consumer behavior. In the context of Indonesia, where the majority of the population is Muslim, the development of economics based on Islamic values ​​is a crucial academic and pedagogical need, particularly in Islamic Religious Education (PAI). This study aims to examine the development of economics based on Islamic values ​​from a sharia economic perspective and its implications for PAI. The study employed a qualitative approach with library research, with data sources consisting of Islamic economics literature, maqasid al-syariah, and national journal articles related to sharia economics and Islamic education. Data were analyzed descriptively and analytically through content analysis to identify Islamic values ​​and their relevance to the development of Islamic Religious Education and learning. The study results indicate that Islamic economics is a value-laden discipline with maqasid al-syariah as a normative and analytical framework. The integration of Islamic economics into PAI has strategic implications for strengthening sharia economic literacy, internalizing values, and shaping students' economic character. This study emphasizes the importance of an integrative model between Islamic economics and Islamic Religious Education in responding to contemporary socio-economic challenges.